Analysis of the 7P Marketing Mix and Strategic Recommendations Using an Omnichannel Approach: A Descriptive Study of Cooler City, Telukjambe Timur, Karawang - Maulidin, Wildan Fatchan; Wahyudin, Wahyudin; Indriyani, Septia; Famella, Gading Adithia (JTI: Jurnal Teknik Industri, 2025)
This study examines the integration of the 7P marketing mix with a multichannel approach at Cooler City Telukjambe Timur Karawang, focusing on its impact on customer experience and business competitiveness. This study addresses the gap in understanding how this strategy is implemented in the Indonesian food and beverage industry, especially in a competitive market. Using a descriptive qualitative method, data was collected through management interviews, direct observation, and digital platform analysis. The study findings revealed that implementing the 7P strategy increased customer engagement through diverse product offerings, flexible pricing, strategic locations, and active social media promotions. However, some areas that need improvement include optimizing digital promotions through influencer collaboration and developing a direct ordering platform. The study concluded that although the 7P and cross-channel strategies have been implemented effectively, continuous digital marketing and staff training innovation is essential to maintain competitiveness and support sustainable growth in the ice cream and beverage sector. Recommendations emphasize enhancing digital promotion strategies and improving customer service processes to ensure a consistent customer experience across all channels.Keywords: Marketing Mix, 7P, Omnichannel, Cooler City, Karawang